LEGAL CONSTRUCTION AUTHORITY OF RELIGION COURT RUNNING THE EXECUTION OF SHARIA ECONOMIC DISPUTS - Hasanuddin Muhammad (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2020)
Since being given the authority to try Islamic economic cases, in 2018 at the first level the religious court has handled 347 cases. Of the 347 cases, 183 cases have been decided. Cases that have been decided need a clear legal umbrella to carry out the contents of the decision. So in this paper the author will try to explain the construction of the authority of the religious court to execute Islamic economic dispute execution. The authority of the religious court in handling Islamic economic disputes was born after the issuance of Law No. 03 of 2006 concerning Religious Courts and was strengthened by the Constitutional Court through Decision Number 93 / PUU-X / 2012. The religious court has also been equipped with Supreme Court Regulation No. 02 of 2008 concerning Compilation of Sharia Economic Law and Supreme Court Regulation No. 14 of 2016 concerning Procedures for Settling Sharia Economic Cases. For the execution, the religious court refers to the HIR and RBgKeywords: execution, religious court, sharia economy